2016
DOI: 10.1055/s-0042-105204
|View full text |Cite
|
Sign up to set email alerts
|

Peroral endoscopic myotomy for Jackhammer esophagus: to cut or not to cut the lower esophageal sphincter

Abstract: Background and study aims: With the success of peroral endoscopic myotomy (POEM) in treatment of achalasia, its successful application to other spastic esophageal motility disorders such as Jackhammer esophagus has been noted. The question of whether the lower esophageal sphincter (LES) should be included in the myotomy for Jackhammer esophagus is a topic of current debate. Here, we report our experience and results with four patients with Jackhammer esophagus treated with POEM. The clinical and manometric res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 20 publications
(19 reference statements)
0
62
0
1
Order By: Relevance
“…It has shown that more than 90% of patients with type III achalasia were successfully cured by POEM with appropriate length of myotomy. Since POEM was first performed in Japan for resolving uncomplicated achalasia, its excellent outcomes allowed us to expand the range of disorders to include advanced sigmoid achalasia, failed surgical myotomy and even other spastic esophageal motility disorders [14] such as distal esophageal spasm [15] and Jackhammer esophagus [16]. The outcome of POEM for achalasia remains excellent up to 3 years after operation [12].…”
Section: Treatment Strategies For Achalasia Based On Subtypesmentioning
confidence: 99%
“…It has shown that more than 90% of patients with type III achalasia were successfully cured by POEM with appropriate length of myotomy. Since POEM was first performed in Japan for resolving uncomplicated achalasia, its excellent outcomes allowed us to expand the range of disorders to include advanced sigmoid achalasia, failed surgical myotomy and even other spastic esophageal motility disorders [14] such as distal esophageal spasm [15] and Jackhammer esophagus [16]. The outcome of POEM for achalasia remains excellent up to 3 years after operation [12].…”
Section: Treatment Strategies For Achalasia Based On Subtypesmentioning
confidence: 99%
“…Several recent reports have demonstrated its efficacy and safety [2,3]. Since then, POEM has been considered a good treatment option when the condition cannot be controlled by medication.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, therapies are still not standardized and include a broad spectrum of potential medical and surgical interventions. Certainly, this is absolutely unsatisfying, since physicians should be able to clarify potential symptom relief, especially when novel DCI decreasing therapies like peroral endoscopic myotomy are suggested for this novel diagnosis . Therefore, this study was designed to explore dysphagia and chest pain in patients with JE and to determine eventual associations between clinical presentation and manometric findings, crucial for subsequent therapies.…”
Section: Introductionmentioning
confidence: 99%